Penerapan Metode Diskusi Dalam Mata Pelajaran Pendidikan Agama Islam Untuk Meningkatkan Hasil Belajar Siswa di SMK Negeri 1 Linggo Sari Baganti - Poldi Poldi (Jurnal Pendidikan Tuntas, 2024)
This study aims to improve students' learning outcomes in Islamic Religious Education through the implementation of the discussion method. The research was conducted in a classroom using a classroom action research approach involving three cycles. The results show a significant increase in students' learning mastery, from 29.41% in the pre-cycle, 70.59% in Cycle I, to 94.12% in Cycle II. The discussion method provided students with opportunities to interact, exchange ideas, and collaboratively construct understanding. Factors contributing to the success included material relevance, the teacher's role as a facilitator, and continuous evaluation. This method proved effective in enhancing students' comprehension, social skills, and learning motivation. The findings suggest that the discussion method can be employed as an innovative approach to improve the quality of education.